Electrowetting‐on‐Dielectrics: Decreasing the Saturated Contact Angle in Electrowetting‐on‐Dielectrics by Controlling the Charge Trapping at Liquid–Solid Interfaces (Adv. Funct. Mater. 18/2016). (May 2016) - Li, Xiangming; Tian, Hongmiao; Shao, Jinyou; Ding, Yucheng; Chen, Xiaoliang; Wang, Li; Lu, Bingheng
Abstract : Electrowetting‐on‐dielectrics has found a wide range of industrial applications, yet the classical contact angle saturation always limits the performance. On page 2994, J. Shao and co‐workers propose a new approach for overcoming this limit by using a time‐modulated square‐wave voltage to control the charge trapping at the liquid‐solid interfaces. Cover image by Ella Marushchenko.